PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Raja Wulandari Putri; Catur Fatchu Ukhriyawati (University of Riau Kepulauan, 2016)
This study aims to determine the effect of partially and simultaneously between liquidity projected by Current Ratio (CR), leverage is projected by Debt to Assets Ratio (DAR) and profitability projected by Return On Assets (ROA) to corporate value projected by Price Book Value (PBV) at the telecommunications company listed on the Indonesia Stock Exchange in 2012-2014. The sample used in this study account for 7 companies were selected based on purposive sampling technique. The data used in this research is secondary data. Data were analyzed using classical asusmsi test, multiple regression analysis, analysis of determination and hypothesis testing using the technique of partial and simultaneous test with the tools IBM SPSS Statistics 20.The results showed that the liquidity variable t value of -1127 and the value of t table amounted to 1,721, (-1127 1,721) and significant values of 0275, (0275 0.05), meaning that liquidity negatively affect the value of the company and partially liquidity no effect significantly to the value of the company. Variable leverage based on the t value of 2.086 and t table value amounted to 1,721, (2,086 1,721) and significant value of 0.052 (0.052 0.05), meaning that the leverage positive effect on the value of the company and partially leverage no significant effect on the value of the company. Variable profitability by t calculate equal to 3,779 and t table value amounted to 1,721, (3,779 1,721) and significant values of 0001, (0.001 0.05), meaning that positive effect on the profitability of the company's value and profitability is partially significant effect on the value of the company. Calculated F value of 5956 while the value of F table at 3,555, (5,956 3,555) with a probability of 0.006 under 0:05 (0.006 0.05), thus simultaneously (together) liquidity, leverage and profitability significantly influence the value of the company. Keywords: Current Ratio, Debt to Assets Ratio, Return On Assets, Price Book Value